2008
DOI: 10.1158/1078-0432.ccr-07-4580
|View full text |Cite
|
Sign up to set email alerts
|

DTS-108, A Novel Peptidic Prodrug of SN38: In vivo Efficacy and Toxicokinetic Studies

Abstract: Purpose: Irinotecan is a prodrug converted to the active cytotoxic molecule SN38 predominantly by the action of liver carboxylesterases. The efficacy of irinotecan is limited by this hepatic activation that results in a low conversion rate, high interpatient variability, and dose-limiting gastrointestinal toxicity. The purpose of this study was to evaluate a novel peptidic prodrug of SN38 (DTS-108) developed to bypass this hepatic activation and thus reduce the gastrointestinal toxicity and interpatient variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…DTS-108 is cleaved chemically by esterases that are found in the blood allowing a higher diffusion and taking advantage of the PK of the highly soluble oligopeptide in the plasma and reduces the SN-38 toxicity by lowering the systemic exposure of SN-38, especially in the bone marrow and gut. 21 Our study reinforced the preclinical models and identified the reduced incidence of digestive toxicity while it identified skin toxicity. In animal models, DTS-108 has been identified to induce immediate effects resembling the symptoms of an infusion reaction.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…DTS-108 is cleaved chemically by esterases that are found in the blood allowing a higher diffusion and taking advantage of the PK of the highly soluble oligopeptide in the plasma and reduces the SN-38 toxicity by lowering the systemic exposure of SN-38, especially in the bone marrow and gut. 21 Our study reinforced the preclinical models and identified the reduced incidence of digestive toxicity while it identified skin toxicity. In animal models, DTS-108 has been identified to induce immediate effects resembling the symptoms of an infusion reaction.…”
Section: Discussionsupporting
confidence: 63%
“…21 DTS-108 is a soluble prodrug of the topoisomerase inhibitor SN-38, the active metabolite of irinotecan. In DTS-108, the SN-38 moiety is covalently linked to a 20-amino acid peptide through a specific cross-linker, which allows the release of SN-38 through esterase bond cleavage.…”
Section: Drug Profile and Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only about 2-8% of the prodrug is converted to SN-38 by carboxylesterases present in liver and cancer cells, and therefore, a high dose of irinotecan needs to be administered to get the desired therapeutic effect (1,2). For example Camptosar ® has to be injected at a high dose of 150-180 mg/m 2 intravenously over a period of 90 min to treat colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%